(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This study investigates the relationship between performance feedback, competitive advantage, and continuance intention in the Iraqi hotel industry. The aim is to explore the effect of performance feedback on the competitive advantage of these hotels while also examining the mediating role played by continuance intention in this association. The study used quantitative research method, and data was collected using survey questionnaires which were given to hotel employees in different regions of Iraq. The findings of the study contribute to the existing knowledge by offering perspective on significance of performance feedback in improving competitive advantage in the hotel industry. Additionally, understanding the mediating role played by continuance intention sheds light on the underlying mechanisms that link performance feedback and competitive advantage. This study is significant for hotel managers and owners in Iraq, as it offers practical implications for enhancing their hotels’ performance and maintaining a competitive edge in the industry.